PENGARUH FAKTOR PRODUKSI TERHADAP PENINGKATAN PRODUKTIVITAS SEKTOR PERTANIAN (Studi Pada Masyarakat Petani di Kabupaten Sumbawa) - K Kamaruddin; Dita Pupitasari; A Asmini (Pusat Riset dan Publikasi, 2022)
The purpose of this study was to determine the influence of rice production factors in Mama Village, Lopok Sub-District, Sumbawa Regency. This research is an associative research which aims to determine the effect of two or more variables. The variables to be examined are production factors consisting of seeds, fertilizers, pesticides, and labor as independent variables, while the dependent variable is the productivity of rice farming in Mama Village, Lopok Sub-District. The type of data used is quantitative data obtained from primary sources, namely the farming community in Mama Village, Lopok Sub-District, totaling 60 people. Researchers used a questionnaire as a data collection instrument which was distributed to 60 respondents. The data that has been collected will be processed using the SPSS program to be studied using multiple linear regression analysis techniques, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determination coefficient test (R2). The results of this study indicate that seeds, fertilizers, pesticides and labor have a positive and significant effect on the productivity of rice farming in Mama Village, Lopok Sub-District, both partially and simultaneously. The degree of influence of production factors consisting of seeds, fertilizers, pesticides, and labor on the productivity of rice farming in Mama Village, Lopok Sub-District, is 65.3%, while the remaining 34.7% is influenced by other variables outside this research model, such as area land, agricultural technology, rainfall and others.